مقاصد الإفتاء: دراسة في المصطلح والأصول والضوابط والتطبيقات في المستجدات المصرفية: (The Purposes of Fatwa: A Study of Terminology, Foundations, Guidelines, and Applications in Contemporary Banking Developments) - محمد عبد الله راشد البذالـي (At-Tajdid - Intellectual Refereed Journal, 2026)
Abstract This study is founded on elucidating the objectives of iftāʾ and the legislation of rulings in contemporary banking developments, with particular emphasis on their firm grounding in the principles of ijtihād that shape the formation of a maqāṣid-oriented mujtahid muftī. The research aims to establish the objectives of iftāʾ in modern banking issues, to derive the ijtihād-based principles and Sharīʿah regulations applicable to jurists at large, and to provide an analytical exposition of their role and juridical derivation in banking fatwas. The significance of this study lies in its endeavour to regulate selected banking issues and to ensure their appropriateness in the application of legal rulings. The research problem is articulated in the following question: What ijtihād-based principles and regulatory foundations does the mujtahid muftī employ when addressing contemporary banking developments, and what is their role in selected fatwas? Given the nature of the study, the researcher adopts an inductive approach in examining the specific components of the subject matter, alongside a foundational methodology that highlights the jurisprudence of the objectives of iftāʾ through an analytical and inferential framework. Among the most significant findings is that the preparation of a mujtahid muftī must be comprehensive, achieved through the effective deployment of foundational juristic competence in harmonising fatwas with their underlying objectives. The study further concludes with a directive underscoring the necessity of integrated ijtihād-based training for specialists operating within the modern banking sector. Among the key recommendations of the study is the organisation of regular conferences aimed at examining and advancing the objectives of iftāʾ and their application to contemporary banking developments. Keywords: objectives of iftāʾ, legislation, Sharīʿah fatwa authority, Islamic banking..